Estudo da biossorção da casca do Ingá-Cipó (ingá edulis mart.) em tratamento de água lago - Nascimento, Isabela Cavalcante (Brasil, 2024)
Water is an essential resource for maintaining life on the planet, any changes in its quality and quantity parameters can cause serious adversities, both for socioeconomic development and the survival of the organisms that depend on it. The Amazon is the region that houses a huge reserve of fresh water in the world, however, the lack of sanitation and water treatment in this region means that many people in rural and riverside areas have problems accessing quality, which which can cause environmental and health damage. As a result, the search for new water treatment methods and technologies based on the use of biomass, as biosorbent material, has been gaining ground and acceptance due to its low cost and good performance for treating these waters. In this context, this work aimed to obtain biomass from the bark of Ingá-cipó, which has vegetative development adaptable to the soil and climate conditions of the tropical Amazon region, for the study of biosorption with lake water. To this end, the peels were subjected to washing, pulping, drying, crushing and sieving. The sample obtained at the end of the treatment was subjected to quantitative adsorption analysis with methylene blue at different concentrations (10, 25, 50, 100 and 250 mg/L) and amounts of biomass (0.1; 0.25; 0. 5 and 1g), with reading intervals of 24, 48 and 72 hours. The solutions were read using a UV-Vis spectrophotometer, in the length range of 100 to 800nm. After analysis, the methylene blue solution was replaced by a sample of water from Lake Serpa, its physicochemical parameters (pH, electrical conductivity, temperature, turbidity, salinity, suspended solids, total suspended solids, apparent color, real, nitrite, nitrate, ammonia and phosphate), and microbiological (coliforms and Escherichia coli) were analyzed before and after treatment with biomass. With the results obtained, it was possible to prove that in tests with methylene blue, biomass has adsorptive capacity. However, the biomass gave the water a yellowish color, due to the presence of secondary metabolites such as flavonoids, tannins, quinones, terpenes and saponins, interfering with the results of the physical-chemical analyses. The values found for the physical-chemical parameters were compared with those presented in Ordinance No. 888/21, which regulates potability standards. The parameters that presented values above the standards allowed by legislation were turbidity, ammonia, nitrite, nitrate, apparent color, coliforms and E. Colis.